2002
DOI: 10.1093/brain/awf001
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of glutamate transporters in the hippocampus of patients with pharmaco‐resistant temporal lobe epilepsy

Abstract: In patients suffering from temporal lobe epilepsy (TLE), increased extracellular glutamate levels in the epileptogenic hippocampus both during and after clinical seizures have been reported. These increased glutamate levels could be the result of malfunctioning and/or downregulation of glutamate transporters (also known as EAATs; excitatory amino acid transporters). In this study, the distribution of protein and mRNA of EAAT subtypes was examined in the hippocampus of TLE patients with hippocampal sclerosis (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
163
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(177 citation statements)
references
References 41 publications
12
163
0
2
Order By: Relevance
“…67 In SJL Thim mice such spatial reorganization of EAAT3 suggests increased levels of glutamate during hippocampal development. Seizurerelated increases in extracellular glutamate are noted in temporal lobe epilepsy, along with elevated levels of EAAT3 in remaining hippocampal neurons, 68 possibly as a compensatory mechanism. The expression of EAAT3 not only in glutamatergic but also in GABAergic neurons, 69,70 as well as some astrocytes, 70 implies that mis-steps in the normal ontogeny of EAAT3 in CA1/CA2 may disrupt both glutamate and GABA synthesis and neurotransmission, 71 critically affecting hippocampal plasticity and enhancing risk for limbic hyperexcitability or seizures.…”
Section: Discussionmentioning
confidence: 99%
“…67 In SJL Thim mice such spatial reorganization of EAAT3 suggests increased levels of glutamate during hippocampal development. Seizurerelated increases in extracellular glutamate are noted in temporal lobe epilepsy, along with elevated levels of EAAT3 in remaining hippocampal neurons, 68 possibly as a compensatory mechanism. The expression of EAAT3 not only in glutamatergic but also in GABAergic neurons, 69,70 as well as some astrocytes, 70 implies that mis-steps in the normal ontogeny of EAAT3 in CA1/CA2 may disrupt both glutamate and GABA synthesis and neurotransmission, 71 critically affecting hippocampal plasticity and enhancing risk for limbic hyperexcitability or seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of extracellular glutamate are detected by in vivo dialysis in sclerotic seizure foci. 18,19 Some authors have reported a down regulation of EAAT1 and EAAT2 glutamate transporters 20,21 in sclerotic hippocampi and propose that this accounts for the observed increase in extracellular glutamate. However, others have been unable to confirm such an observation.…”
Section: Astrocyte Transporter Moleculesmentioning
confidence: 99%
“…However, the studies investigating the functional expression of astrocytic glutamate transporters in human epilepsy are inconsistent. Some studies reported a downregulation of EAAT1 and EAAT2 (Proper et al, 2002), but others reported no significant changes (Eid et al, 2004). For effective removal of excess extracellular glutamate, the transmitter must be sequestered and metabolized once taken up by astrocytes.…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%